Beautiful life - Portes, Gil M.; Regal Entertainment (Firm). (Pasig City Regal Entertainment, 2004)
Beautiful life is a timely drama about the heartbreaking, impact of a terrorist act on eight women whose loved ones are killed at an airport bombing. Playing the grieving mothers, wives, daughters, and girlfriends who must deal with an imaginable loss.
VCD
Directed by Gil M. Portes
Gloria Romero, Dina Bonnevie, Amy Austria
Keywords: Feature Films